Propuesta documentada para el sistema de gestión de seguridad y salud en el trabajo con base en el numeral 2.2.4.6. Del decreto 1072 de 2015 para la fundación Alpina ubicada en sopó-Cundinamarca - Niño Duarte, Sergio Nicolas; Johnson Serna, Stefanny (Universidad Antonio Nariño, 2022)
The main objective of this degree project was the Documented Proposal for the Occupational Health and Safety Management System based on section 2.2.4.6. of Decree 1072 of 2015 for the Alpina Foundation located in Sopó-Cundinamarca, in order to design and create documentation, diagnoses and useful, clear and concise information for subsequent implementation, in addition to minimizing the risks to which workers are exposed. In the first place, an initial diagnosis was made based on Decree 1072, in order to know the current situation of the Alpina Foundation in matters of Safety and Health at Work, showing a worrying result. Subsequently, the identification of hazards and risks was carried out through the matrix of the Colombian Technical Guide 45 Annex B, in order to eliminate, replace or establish controls to the risks and dangers implicit in each process, task and activity, both for the administrative and operational area. Finally, the plans, policies and procedures were drawn up, together forming the necessary documentation for the structuring of the SG-SST for the Alpina Foundation, following the guidelines and current legal regulations applicable in Colombia.